1984
DOI: 10.1007/bf02395206
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of fentanyl by the cardiopulmonary bypass (CPBP)

Abstract: Immediately following the connection of pediatric patients to cardiopulmonary bypass we have consistently observed a steep decrease in fentanyl plasma concentration (74 +/- 8.7%) (mean +/- SD), much greater than would have been expected from hemodilution alone (50.6% +/- 12.0%) (p less than 0.0001). Priming of the pump with 20 ng/ml of fentanyl before connection to the patients did not prevent this phenomenon. In order to study the possibility that fentanyl is sequestered by the bypass, levels of the primed dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…In our study, the dilutional effect of CPB was estimated as a percentage of total volume as suggested by Koren et al (17). Total volume was calculated by adding the priming volume to an assumed blood volume of 80 ml/kg of body weight (8).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the dilutional effect of CPB was estimated as a percentage of total volume as suggested by Koren et al (17). Total volume was calculated by adding the priming volume to an assumed blood volume of 80 ml/kg of body weight (8).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have measured total fentanyl concentrations in plasma and reported a significant drop on connection to bypass (4)(5)(6). Fentanyl is usually about 80% bound to plasma proteins but this is likely to vary under abnormal physiological conditions (7).…”
Section: Introductionmentioning
confidence: 99%
“…Many physiological changes occur in patients placed on CBP, and this technique is known to alter drug levels in plasma (8,15). At least two factors can explain this result: a rapid increase in the volume of distribution because of the additional volume in the priming pump (11) and drug sequestration within the CPB circuit, which has been demonstrated for fentanyl (8) and nitroglycerin (5) but is only suspected for vancomycin (10). Whatever the mechanism, plasma vancomycin concentrations decrease when the patient is placed on CPB.…”
mentioning
confidence: 99%